Assessment of consumer exposure to chemical agents on the example of the ConsExpo model - Agnieszka Niepsuj; Sławomir Czerczak (Nofer Institute of Occupational Medicine, 2019)
Not only employees in industrial plants but also consumers, by using finished products, are exposed to chemical substances. Therefore, consumer exposure assessment is also important. To assess the risk for the consumer, the exposure magnitude is needed but measuring these values in residential conditions of consumers is usually impossible. ConsExpo has been designed to facilitate the exposure assessment to substances in consumer products. It is available in English as a free web application at www. consexpoweb.nl. The ConsExpo Web tool, developed by the Netherlands National Institute for Public Health and the Environment (Rijksinstituut voor Volksgezondheid en Milieu), contains a set of models that help in the assessment of exposure to the substances in consumer products. These are mathematical models with increasing complexity, describing exposure by inhalation, dermal and oral routes. Available models are described in this work. ConsExpo is also equipped with a products database with defined exposure scenarios and default values, which could be a starting point for the models. The aim of this work was to review the literature regarding ConsExpo and to present the application to Polish users through the description of the models contained therein and by providing assessments examples. The review was based on databases of scientific journals. ConsExpo is a commonly known tool, and one of its applications is exposure estimation in comparative studies and the development of new models. For lower-tier analyses ConsExpo can be used by less advanced users. The most favorable for Polish users would be the creation of the Polishlanguage version of the ConsExpo application or a detailed Polish-language instruction manual. Med Pr. 2019;70(6):747-62